Synthesis of Boronic Ester γ‐Lactam Building Blocks. Issue 9 (16th December 2020) - Rodgers, George; Wilson, Ellen J.; Robertson, Craig C.; Cox, Daniel J.; Partridge, Benjamin M.
Abstract: Saturated heterocycles are found widely in biologically active compounds such as medicinal drugs and agrochemicals. However, boronic acid‐derived building blocks for these structures have limited availability, particularly in comparison to heteroaromatic boronic acids. We report the preparation of boronic ester γ‐lactams through a Cu‐catalysed conjugate borylation‐cyclisation protocol. Using a chiral catalyst, this can be performed in high enantioselectivity. Exploration of the further transformations of these reagents suggest that the boronic esters have much potential as chemical building blocks. Abstract :